What is the most important leg and disciplinein triathlon mixed team relays? - Martínez Sobrino, J.; Veiga, S.; Santos del Cerro, J.; González-Ravé, J. M. (Journal of Human Kinetics, 2023)
This study aimed to determine the importance of the different relay legs and sport disciplines in the overall result of the triathlon Mixed Team Relay (MTR) events. The study analysed the results of 80 Mixed Team Relay triathlon teams (n = 320 professional triathletes) corresponding to the top ten finishers at the World Championships in Hamburg from 2013 to 2020. Split times, average speeds, time behind the race leader (gap), partial and finishing positions, as well as the rank positions of every segment, relay leg, and overall race were computed. Decision tree analyses were conducted as a predictive method for the overall results, and correspondence analyses were conducted to examine the relationship between the different relay legs and segments and the finishing positions. Running was the variable with the greatest importance (32%) in the overall result, followed by female team members (17%) and the third relay leg (17%). The swimming segments (1%) and the fourth relay leg (1%) had the lowest relevance. Medallist relay teams were characterised by cycling and running faster than 10.99 m/s and 5.59 m/s, respectively, with time gaps of less than 43 seconds by the end of the third relay leg. A reliable and accurate prediction model for the medallists` and finalists` team positions in the Mixed Team Relay triathlon was obtained. The running disciplines and performance of female team members, especially in the third leg, were ascertained to be the most significant determinants for the overall Mixed Team Relay result.